Biographical Films Between Deification and Demonization (Global Journal of Human-Social Science, 2024)
Bio graphical films are a sig nificant part of cinema providing viewers with a glimpse into the lives of real people However their depiction often varies with some portraying their characters as moral heroes and others as villains This study explores the thematic exploration of deification versus demonisation in biographical films focusing on their historical context evolution and impact on audience perception Deification emphasises the positive qualities of individuals while minimising their imperfections while demonisation highlights unfavourable characteristics and behaviours The ethical and moral implications of depicting real-life individuals and the sociocultural and political factors influencing these portrayals are explored The study also explores the audience s perception and the influence of media and criticism on public discourse This research enhances our understanding of the complex nature of portraying real-life individuals contributing to a deeper understanding of the interplay between deification and demonisation in biographical cinema